2020
DOI: 10.1101/2020.04.16.045054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune modulation to improve survival of respiratory virus infections in mice

Abstract: Viral pneumonia remains a global health threat requiring novel treatment strategies, as strikingly exemplified in the SARS-CoV-2 pandemic of 2019-2020. We have reported that mice treated with a combination of inhaled Toll-like receptor (TLR) 2/6 and TLR 9 agonists (Pam2-ODN) to stimulate innate immunity are broadly protected against respiratory pathogens, but the mechanisms underlying this protection remain incompletely elucidated. Here, we show in a lethal paramyxovirus model that Pam2-ODN-enhanced survival i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Moreover, a therapeutic role for TLR5 has been proposed very recently by Chakraborty et al; it can be used as an immunomodulator that is able to activate the immune system to fight the SARS-CoV-2 . Interestingly, in a 2020 preprint research article, the use of a combination of inhaled 1a and CpG-ODNs in mice to stimulate their immune system against SARS-CoV-2 has been reported . For these reasons, a wider exploration of TLRs and their modulators may drive the discovery of new potential drugs or vaccine adjuvants to be applied against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a therapeutic role for TLR5 has been proposed very recently by Chakraborty et al; it can be used as an immunomodulator that is able to activate the immune system to fight the SARS-CoV-2 . Interestingly, in a 2020 preprint research article, the use of a combination of inhaled 1a and CpG-ODNs in mice to stimulate their immune system against SARS-CoV-2 has been reported . For these reasons, a wider exploration of TLRs and their modulators may drive the discovery of new potential drugs or vaccine adjuvants to be applied against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…320 Interestingly, in a 2020 preprint research article, the use of a combination of inhaled 1a and CpG-ODNs in mice to stimulate their immune system against SARS-CoV-2 has been reported. 321 For these reasons, a wider exploration of TLRs and their modulators may drive the discovery of new potential drugs or vaccine adjuvants to be applied against SARS-CoV-2. As recently reported by Conti et al, the binding of SARS-CoV-2 to TLR2, TLR3, or TLR4 determines the release of inflammatory cytokines such as IFN-α, TNF, and IL-1.…”
Section: ■ Conclusion and Perspectivesmentioning
confidence: 99%
“…50 51 The PUL-042 showed satisfactory defense against a broad range of pulmonary pathogens, including the coronaviruses that cause MERS and SARS in pre-clinical mice models. 52 Moreover, PUL-042 can reduce the viral load in the pulmonary airways post-infection. 52 Based on this preliminary study, Pulmotect, Inc. (Houston, USA) started clinical trials i.e.…”
Section: Intranasal Vazegepantmentioning
confidence: 99%
“…52 Moreover, PUL-042 can reduce the viral load in the pulmonary airways post-infection. 52 Based on this preliminary study, Pulmotect, Inc. (Houston, USA) started clinical trials i.e. NCT04313023 and NCT04312997 to prevent COVID-19.…”
Section: Intranasal Vazegepantmentioning
confidence: 99%
“…Some of the results of these studies have been previously reported in the form of a preprint ( 23 ).…”
mentioning
confidence: 96%